(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
Fast development of applications and its growing reputation in recent years has motivated various IT organizations want to move application between one platforms to another, so portability is a rising concern. Portability is a measure of how easily an application can be moved from one environment to another. For maximum software systems, portability is considered as an attractive quality. Corporate environment such as business or government are designed to operate in a huge software system platform called enterprise application and that uses a pack of technologies that helps them participate directly with customers and are complex, accessible, and component-based, scattered and mission critical. The purpose is to identify some of the portability issues in an application while porting to another platform and considered some key points to achieve the portability using some of the technologies. One of the Technologies is used to overcome the Portability issues in an application that is Full stack Technology where it has different layers based on that there are technologies such as Apache Cordova, REST API, Node.js, Ionic framework and done case study on technology called React Native with real time application.